Right postero lateral innate diaphragmatic hernia or hernia through Bochdalek foramen - Olmedo, Mario; Perrone, Luis; Goycoechea, Walter; Laviña, Raúl (Cirugía del Uruguay, 1984)
A case of strangulated diaphragmatic hernia through Bochdalek's foramen is presented. lnitially hernia clini• cally appeared as a pyloric syndrome wich brought about a review of local and foreign bibliography that ev.id1mced this is an extremely rare pathology, spe• . cially in adults, on the right side, with gastric strangu• lation.